No evidence for the efficacy of slow-paced breathing as a recovery strategy after sprint interval training - Raidl, P.; Wessner, B.; Laister, S.; Csapo, R. (International Journal of Sports Physiology and Performance, 2026)
Purpose: Breathing practices are increasingly adopted by athletes due to the potential benefits for recovery, performance, and well-being. Slow-paced breathing is believed to increase cardiac vagal activity and relaxation, potentially supporting adaptive processes. Sprint interval training, by contrast, elicits a strong stress response. Therefore, we hypothesized that adding slow-paced breathing to highly demanding sprint interval training would enhance recovery, as indicated by cardiac autonomic control and sleep metrics, ultimately contributing to greater performance gains. Methods: Thirty-four participants were randomized into an intervention or control group. While both groups completed 4 weeks of supervised sprint interval training, only the intervention group practiced slow-paced breathing after each training and every evening before bedtime. Running performance, vagally mediated heart-rate variability (root mean square of successive differences), and sleep metrics were assessed throughout the intervention to evaluate the potential benefits of the breathing exercise. Results: Sprint interval training led to significant improvements in maximal power decrements (-8.26%, 95% CI, -11.48 to -5.04, P < .001) and overall work (8.84 kJ/kg, 95% CI, 4.58 to 13.1, P < .001), but performance gains did not differ between groups (P > .05). Unexpectedly, nocturnal heart rate showed a slight increase over time in the intervention group (+3.1 beats·min-1, 95% CI, 0.47 to 5.72, P < .05) compared with the control group. Conclusion: Despite positive effects reported in other training and performance contexts, 4 weeks of daily slow-paced breathing did not confer additional performance improvements or physiological benefits when combined with sprint interval training. These findings suggest that 10-minute sessions of slow-paced breathing following highly demanding sprint interval training offer limited value for enhancing performance or supporting recovery.